2018
DOI: 10.1155/2018/8672578
|View full text |Cite
|
Sign up to set email alerts
|

Transient Pressure and Rate Decline Analysis for Horizontal Well in Stress-Sensitive Composite Reservoir

Abstract: The existence of stress sensitivity effect made the percolation mechanism of low-permeability reservoirs significantly complex. Further, numerous reservoirs have composite stratum properties in actual development procedure. This paper based on the concept of permeability stress sensitivity presents an unsteady flow model for horizontal well taking both stress sensitivity and composite reservoir into account. Analytic solutions for the transient pressure and the rate decline behaviors are obtained by comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Zhao et al [31], Jabbari et al [32], Samaniego and Villalobos [33], and Zhang et al [34] carried out research on the stress-sensitivity of fracture reservoirs, and Wang and Wang [35] proposed the mathematical model considering the effect of slipping and stress sensitivity in fractured gas reservoirs. Huang et al [36] presented the transient flow model for horizontal wells in stress-sensitivity composite reservoirs, and Li et al [37] presented the dual-porosity media model for horizontal wells in fractured tight gas reservoirs with stress sensitivity. Yuan et al [38] suggested a general solution for oil flow, taking multiphase flow, the properties of stress-sensitivity reservoirs, and the changes in operation conditions into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [31], Jabbari et al [32], Samaniego and Villalobos [33], and Zhang et al [34] carried out research on the stress-sensitivity of fracture reservoirs, and Wang and Wang [35] proposed the mathematical model considering the effect of slipping and stress sensitivity in fractured gas reservoirs. Huang et al [36] presented the transient flow model for horizontal wells in stress-sensitivity composite reservoirs, and Li et al [37] presented the dual-porosity media model for horizontal wells in fractured tight gas reservoirs with stress sensitivity. Yuan et al [38] suggested a general solution for oil flow, taking multiphase flow, the properties of stress-sensitivity reservoirs, and the changes in operation conditions into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical model presented in [27] and based on pressure build-up curves makes it possible to predict the change in the permeability during the hydrocarbon production. The authors in [28][29][30][31][32][33] also study the nature of changes in fluid filtration in a reservoir as a result of changes in effective pressure and permeability and its relationship with the results of pressure build-ups. In these works, the same approach was used, although the method used is universal but it does not take into account the reservoir properties, the values of the coefficients in the equations are individual for each rock and, possibly, depend on its properties, therefore, additional research is needed in order for this method to be used for predicting permeability of formations with different properties.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [33][34][35][36][37] also studied the change in fluid filtration in a reservoir as a result of changes in effective pressure and permeability, as well as how this was related with results of pressure build-ups. However, the study was also performed under ideal reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that in works [29][30][31][32][33][34][35][36][37], as in many other works, the main attention is paid to the study of changes in the pressure build-up curves of a stress-sensitive formation. These studies show how permeability changes from pressure in situ and the results of historical observations during production are not presented.…”
Section: Introductionmentioning
confidence: 99%